2000
DOI: 10.1021/ma001153+
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl-philic Character of Poly(2-hydroxyethyl vinyl ether)-block-poly[2-(2,2,2-trifluoroethoxy)ethyl vinyl ether] Micelles in Water:  Selective Solubilization of Perfluorinated Compounds

Abstract: Two types of amphiphilic block copolymer, poly(2-hydroxyethyl vinyl ether)-block-poly[2-(2,2,2-trifluoroethoxy)ethyl vinyl ether] (poly(HOVE-b-TFEOVE)) (m:n ) 78:23) and poly(2-hydroxyethyl vinyl ether)-block-poly(n-butyl vinyl ether) (poly(HOVE-b-NBVE)) (m:n ) 74:23), having the same ratios of polymerization degree in hydrophilic and hydrophobic segments with the same total chain length were synthesized, and the properties of their aqueous solutions were investigated, where m and n represent number-averaged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Matsumoto et al [27,28] have confirmed by small angle X-ray scattering that the water-soluble fluorinated diblock copolymer aggregates into spherical micelles in water. Busse et al [30] have recently reported that triblock copolymer including fluorinated block also forms micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsumoto et al [27,28] have confirmed by small angle X-ray scattering that the water-soluble fluorinated diblock copolymer aggregates into spherical micelles in water. Busse et al [30] have recently reported that triblock copolymer including fluorinated block also forms micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a fluorinated block plays a role in the construction of ordered structures as a component different from a hydrophilic or oleophilic block [12]. Copolymers with fluorinated side chains have been synthesized with the expectation of such characteristics [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…1,1,2-Trichlorotrifluoroethane is often effective to avoid precipitates during polymerization and to produce polymers with controlled structures (Choi et al, 1988;Percec and Lee, 1992;Vandooren et al, 1994). Similarly, a block copolymer composed of poly(2-hydroxyethyl vinyl ether) and poly(2-(2,2,2-trifluoroethoxy)ethyl vinyl ether) can be synthesized by sequential cationic polymerization of 2-(acetoxyethyl) vinyl ether and 2-(2,2,2-trifluoroethoxy)ethyl vinyl ether, followed by hydrolysis of the acetyl protecting group as shown in Figure 23.2 (Matsumoto et al, 1999;Matsumoto et al, 2000).…”
Section: Living Cationic Polymerizationmentioning
confidence: 99%
“…Polystyryllithium end capped with 1,1-diphenylethylene can completely initiate the (Percec and Lee, 1992;Matsumoto et al, 2000). polymerization of perfluoroalkyl methacrylate to give a well-defined AB diblock copolymer (A: polystyrene, B: poly(perfluoroalkyl methacrylate)), as shown in Scheme 23.2.…”
Section: Living Anionic Polymerizationmentioning
confidence: 99%
“…As such, there is a need to develop new fluorinated materials that are less expensive and possess improved properties. [5][6][7][8][9][10][11] Blending of polymers offers a convenient and economical means of obtaining new materials that combine the advantages of the blend components. 12,13 For fluorinated/nonfluorinated polymer blends, the significantly lower surface energies of fluorinated polymers over their aliphatic analogs provide a substantial thermodynamic driving force for forming fluorinated surfaces.…”
Section: Introductionmentioning
confidence: 99%